Impact of Economic Sanctions Against Russia on the EU27’s Economy (2023) - Malouin-Chénier, Étienne; Chytilová, Helena; Kotrba, Vojtěch; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2024)
The main hypothesis of this thesis states that economic sanctions are responsible for the adverse changes in the European Union’s main macroeconomic indicators since the beginning of the Russian invasion of Ukraine. The study also aims to determine if, after more than two years of conflict (2022 and 2023), the sanctions had a stronger economic impact on the European Union in comparison to the country they target, Russia. This analysis is achieved through multiple difference-in-difference econometric regressions with panel datasets. The main conclusions of the thesis confirm the following results: sanctions increased inflation within the EU by an average of 3.79 points a year. They have also reduced GDP growth by approximately 1.15% a year and increased the unemployment rate by 2%. Furthermore, this thesis demonstrates that the Russian Federation has been far more impacted by the sanctions than the EU for inflation and GDP growth, but not unemployment. Despite their adverse temporary effects on the EU, this thesis proves that sanctions remain a powerful economic tool, and on a longer horizon, their effects will be displayed to a greater extent especially when political considerations are taken into account. This work is among the first studies of its kind since it uses retrospective data to assess the impact of sanctions more than two years after the conflict started. This thesis also focuses heavily on the impacts of the sanctions for senders, rather than only focusing on target countries.
Vedoucí práce: Helena Chytilová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: economics and public policy [obor dipl. práce]; diplomové práce; master's theses